2009
DOI: 10.2298/sgs0904201m
|View full text |Cite
|
Sign up to set email alerts
|

Closure of large oroantral fistula with resorbable collagen membrane: Case report

Abstract: Oroantral fistula is pathologic communication between oral cavity and maxillary sinus, usually localized between antrum and buccal vestibulum. Persisting OAF always causes chronic maxillary sinusitis. A technique for closure of a large oroantral fistula with resorbable collagen membrane is described

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…All the sinuses with failures could be treated with a resorbable collagen membrane to close the failure prior to graft insertion without compromising the outcomes. This finding is supported by studies on the treatment of oroantral communications, which have demonstrated success in closing sinus floor bone defects by using the same type of membrane …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…All the sinuses with failures could be treated with a resorbable collagen membrane to close the failure prior to graft insertion without compromising the outcomes. This finding is supported by studies on the treatment of oroantral communications, which have demonstrated success in closing sinus floor bone defects by using the same type of membrane …”
Section: Discussionmentioning
confidence: 63%
“…This finding is supported by studies on the treatment of oroantral communications, which have demonstrated success in closing sinus floor bone defects by using the same type of membrane. 24,25 In this study, all sinus floor augmentation surgeries were performed with the lateral window approach by using a piezoelectric surgical device. This method has been regarded as useful to avoid sinus membrane perforation and other surgical complications insofar as piezoelectric surgery is able to cut through hard tissue while sparing soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…After completing a mucoperiosteal vestibular flap and elimination of the mucosal pathway of the fistula, the technique consists of placing the membrane on the bone defect. The flap is thus returned to its original position without covering the collagen membrane [ 12 ]. This technique differs slightly from the first case reported in this work, where the mucoperiosteal flap covers the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…, para el diagnóstico de la CBS es muy importante el conocimiento y experiencia del operador (5,9) . Su diagnóstico debe ser inmediato para evitar futuras complicaciones como una sinusitis maxilar o una fistula bucosinusal (FBS), que se produce pasada las 48 a 72 horas (18,19) .…”
Section: Diagnósticounclassified
“…Entre las desventajas de esta técnica se describen: la exposición de la superficie palatina, dolor y la presencia de superficies irregulares que quedan después de realizar el colgajo, además puede ocurrir necrosis del colgajo por una rotación excesiva del mismo (17)(18)(19)27) . (Figura 4) COLGAJO DE LA BOLA ADIPOSA DE BICHAT:…”
Section: (Figura 3) Colgajo Palatinounclassified